Mycobacterium tuberculosis specific CD8(+) T cells rapidly decline with antituberculosis treatment. - Melissa R Nyendak; Byung Park; Megan D Null; Joy Baseke; Gwendolyn Swarbrick; Harriet Mayanja-Kizza; Mary Nsereko; Denise F Johnson; Phineas Gitta; Alphonse Okwera; Stefan Goldberg; Lorna Bozeman; et al. (PLoS ONE)
Rationale Biomarkers associated with response to therapy in tuberculosis could have broad clinical utility. We postulated that the frequency of Mycobacterium tuberculosis (Mtb) specific CD8(+) T cells, by virtue of detecting intracellular infection, could be a surrogate marker of response to therapy and would decrease during effective antituberculosis treatment. Objectives We sought to determine the relationship of Mtb specific CD4(+) T cells and CD8(+) T cells with duration of antituberculosis treatment. Materials and methods We performed a prospective cohort study, enrolling between June 2008 and August 2010, of HIV-uninfected Ugandan adults (n = 50) with acid-fast bacillus smear-positive, culture confirmed pulmonary TB at the onset of antituberculosis treatment and the Mtb specific CD4(+) and CD8(+) T cell responses to ESAT-6 and CFP-10 were measured by IFN-γ ELISPOT at enrollment, week 8 and 24. Results There was a significant difference in the Mtb specific CD8(+) T response, but not the CD4(+) T cell response, over 24 weeks of antituberculosis treatment (p<0.0001), with an early difference observed at 8 weeks of therapy (p = 0.023). At 24 weeks, the estimated Mtb specific CD8(+) T cell response decreased by 58%. In contrast, there was no significant difference in the Mtb specific CD4(+) T cell during the treatment. The Mtb specific CD4(+) T cell response, but not the CD8(+) response, was negatively impacted by the body mass index. Conclusions Our data provide evidence that the Mtb specific CD8(+) T cell response declines with antituberculosis treatment and could be a surrogate marker of response to therapy. Additional research is needed to determine if the Mtb specific CD8(+) T cell response can detect early treatment failure, relapse, or to predict disease progression.